Pengaruh Latihan Permainan Rondo dan Small Sided Game terhadap Keterampilan Passing Pemain Futsal - Benedictus Pio Prasetyajati; Andri Arif Kustiawan; Agus Pribadi; Bimo Alexander (MAN Insan Cendekia Jambi, 2026)
This research was oriented to test the effectiveness of cat and mouse games and small field games (SSG) for the ball passing ability of extracurricular male futsal athletes at SMK Negeri 9 Surakarta. A quantitative approach with an experimental method through a two group design, namely the initial data collection method and final data collection method. The research sample involved 24 extracurricular participants who were evenly distributed in rondo and SSG games. Data measurement was carried out using the Futsal Basic Sports Skills Test (TKDO) passing test instrument, Data analysis answered that the rondo game intervention had a significant impact on improving passing skills (tcount = -29,000; p < 0.05). Similar results were also found in the SSG group which showed a significant effect on passing ability (tcount = -29,712; p < 0.05). The rondo group recorded a percentage increase of 26.01%, while the SSG group experienced an increase of 22.75%. Based on this comparison, it can be concluded that the rondo game practice answers more questions than small-sided games to determine the improvement in passing of extracurricular male futsal players at SMK Negeri 9 Surakarta.